Stability of a system of generalized trigonometric equations - Fidytek, Irena (Annales Mathematicae Silesianae, 1995)
Addition formulas for generalized trigonometric functions corresponding to a given symmetric bounded and convex planar set containing the origin as an inner point are derived. Connections with the theory of characters on (semi) groups are considered. Hyers-Ulam stability of a suitable system of functional equations is investigated. It is also shown that superstability phenomenon fails to hold for that system.